Consumers' permission in mobile advertising - Lim, Fong Hoong (2011)
With the emergence of the increasing mobile users in Malaysia especially tertiary institution students, mobile marketing can be a powerful advertising medium that allows marketer to generate one-to-one personal relationship with consumers. However, in spite of its potential, little academic research in this topic had been done. This research examines the consumers’ willingness to give permission in mobile advertising. The purpose of this research is to identify the relationship between consumers’ perception and permission in mobile advertising. This study utilized both quantitative and qualitative research method via questionnaire and interview. The results show that respondents have a negative perception and would not trust mobile advertising. However, respondents still sees the mobile advertising as a promising advertising medium. This research rounds off with conclusion, limitations in this research project and directions for future recommendations and research into mobile advertising.